ON THE ISSUE OF FINANCIAL SUSTAINABILITY DEVELOPMENT IN A REGION - F. N. Garipov; Z. F. Garipova (Экономика региона, 2010)
The paper deals with the issue of financial sustainability of a regional economic system. Interpretation of the category of financial sustainability is given in its interrelation with economic stability. The paper also suggests a tool for quantitative assessment of financial sustainability of a region, which takes specific features regarding generation of basic parameters of regional financial state into consideration